2015
DOI: 10.5114/pdia.2014.40968
|View full text |Cite
|
Sign up to set email alerts
|

Amorolfine vs. ciclopirox – lacquers for the treatment of onychomycosis

Abstract: Amorolfine 5% and ciclopirox 8% nail lacquers are commonly used in topical treatment of onychomycosis. These formulations may be used alone or in combination with oral antifungal agents. Amorolfine and ciclopirox are valuable therapeutic options, however, their usage in monotherapy should be limited. Proper amorolfine and ciclopirox penetration through the nail plate is provided by transungual drug delivery systems. Although amorolfine and ciclopirox have a different mode of action, they both exhibit a broad a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 41 publications
0
36
0
10
Order By: Relevance
“…In the current study, we adopt amorolfine as the representative of topical treatments, because abundant, reliable information was available on the feasibility, outcomes, and potential side effects of amorolfine in the treatment of onychomycosis (Auvinen et al, ). There are some other topical antifungals available in the market, but it is difficult to assess their efficacy in monotherapy due to the different criteria of recruiting patients for investigations, different study periods and post‐treatment assessment (Tabara et al, ), there is one article which put amorolfine and ciclopirox in separate combination in comparison, it turns out that ciclopirox in combination is more efficient than amorolfine in combination, but we still need more evidence to verify it. Iorizzo et al supported that P‐3051 (a water‐soluble ciclopirox 8% formulation in hydroxypropyl chitosan technology) should be considered as the gold standard for the topical treatment of onychomycosis (Iorizzo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we adopt amorolfine as the representative of topical treatments, because abundant, reliable information was available on the feasibility, outcomes, and potential side effects of amorolfine in the treatment of onychomycosis (Auvinen et al, ). There are some other topical antifungals available in the market, but it is difficult to assess their efficacy in monotherapy due to the different criteria of recruiting patients for investigations, different study periods and post‐treatment assessment (Tabara et al, ), there is one article which put amorolfine and ciclopirox in separate combination in comparison, it turns out that ciclopirox in combination is more efficient than amorolfine in combination, but we still need more evidence to verify it. Iorizzo et al supported that P‐3051 (a water‐soluble ciclopirox 8% formulation in hydroxypropyl chitosan technology) should be considered as the gold standard for the topical treatment of onychomycosis (Iorizzo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Amorolfine belongs to the morpholine derivates and acts against dermatophytes, yeasts and moulds by inhibiting Δ14-reductase and Δ7-8 isomerase in the ergosterol synthesis. It exhibits fungistatic activity [33]. In the USA, it is not approved for onychomycosis therapy.…”
Section: Amorolfinementioning
confidence: 99%
“…Different surveys have reported that 22 and 26 % of athletes in East Asia and Europe, respectively are prone to onychomycosis, with a total population prevalence rate of 14 % in the US (Caputo et al 2001; Thomas et al 2010). Onychomycosis accounts for almost 50 % of all nail-related diseases (Faergemann and Baran 2003;Hay 2005), and its prevalence increases with age, affecting 2-13 % of all populations while 20 % of patients are aged 40-60 years and older and 50 % are 70 years old (Tabara et al 2015). This health problem affects toenails more than it does fingernails because toenails have a slower growth rate, which enhances fungal invasion.…”
Section: Introductionmentioning
confidence: 97%